Toxicological study of seeds Moringa oleifera Lam. using the Artemia salina Leach test (Research, Society and Development, 2020)
The search for plant species, especially those with the greatest economic and social benefits, has gained emphasis in scientific research. In this context, Moringa oleífera Lam. stands out, a plant originally from India and which has several applications in the food, industrial, medicinal, water treatment sectors, among others. Its fruits consist of pods that contain seeds rich in minerals, vitamins, proteins, lipids, carbohydrates, secondary metabolites and antioxidants. The present work had as objective to make a toxicological study of the seeds of M. oleifera Lam. using the Artemia salina Leach test. Two ethanolic extracts were prepared, one from almonds and the other with only the husks covering the seeds. The extracts were solubilized in 5 different concentrations. Each test tube contained the extracts in their respective concentrations and 10 active A. salina. After 24 h, the count was performed to determine the CL50. The data obtained were analyzed using PROBIT analysis using the Statistica software. From the analyzes performed, it was concluded that neither the almond nor the husk of the seed of M. oleifera Lam. presented toxicity, since both had CL50 values ​​above 1000 µg.mL-1, revealing even less toxicity than other plants conventionally used in Brazil, such as dill and fennel.